A big change - Lidin, Konstantin (project baikal, 2022)
The current period in the development of architectural theory and practice simultaneously demonstrates signs of dynamics and statics. An analysis of reflection of such phenomena as the COVID-19 pandemic and global climate change allows us to conclude that the current mass picture of the world is bifurcated and internally contradictory. A high background level of anxiety suppresses creative tendencies and creates the effect of “stagnation in the era of change”.
Keywords: architecture; history; social psychology; pandemic; epidemic of mental disorders; global climate; crisis